(untitled) (International Bulletin of Applied Science and Technology, 2023)
usually before learning foreign languages, students have great interest in that language and motivation at the initial stage. They want to express their opinions in a foreign language, chat with peers in that language and learn about the people who speak that language, the country and the culture that will motivate kata to develop oral speech.